2021
DOI: 10.3390/foods10020441
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Pyrazines and Their Perceptual Interactions in Soy Sauce Aroma Type Baijiu

Abstract: Pyrazines are important compounds in soy sauce aroma type Baijiu (SSAB). In this work, a total of 16 pyrazines were analyzed using ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC–MS/MS) in SSAB. The quantitative results showed that 2,3,5,6-tetramethylpyrazine, 2,6-dimethylpyrazine and 2,3,5-trimethylpyrazine were the three most concentrated pyrazines. The highest odor activity value (OAV) was determined for 2-ethyl-3,5-dimethylpyrazine. Quantitative analysis combined with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…The efficacy of this combination during the subjugation stage of attack could explain why moths use IBMP in combination with SBMP even when IBMP alone is mostly ineffective. Similarly, a recent study by Yan et al (2021) found that sub-threshold pyrazines, which are not detected at the given concentration on their own, can nonetheless contribute synergistically to the organoleptic properties of a chemical mixture as suggested by Maga et al (1973). Interestingly, Yan et al (2021) also found that sub-threshold pyrazines reduced the odour thresholds of supra-threshold pyrazines, which could explain why the combination of SBMP+IBMP did not affect bird hesitation to approach the defensive odour.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The efficacy of this combination during the subjugation stage of attack could explain why moths use IBMP in combination with SBMP even when IBMP alone is mostly ineffective. Similarly, a recent study by Yan et al (2021) found that sub-threshold pyrazines, which are not detected at the given concentration on their own, can nonetheless contribute synergistically to the organoleptic properties of a chemical mixture as suggested by Maga et al (1973). Interestingly, Yan et al (2021) also found that sub-threshold pyrazines reduced the odour thresholds of supra-threshold pyrazines, which could explain why the combination of SBMP+IBMP did not affect bird hesitation to approach the defensive odour.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, a recent study by Yan et al (2021) found that sub-threshold pyrazines, which are not detected at the given concentration on their own, can nonetheless contribute synergistically to the organoleptic properties of a chemical mixture as suggested by Maga et al (1973). Interestingly, Yan et al (2021) also found that sub-threshold pyrazines reduced the odour thresholds of supra-threshold pyrazines, which could explain why the combination of SBMP+IBMP did not affect bird hesitation to approach the defensive odour. Altogether these results suggest that the aversion of a chemical mixture is not the same as the sum of its parts, and chemical defences should therefore be presented in natural combinations to account for potential synergistic and antagonistic relationships that influence the sensory responses of predators.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although the sesame flavor of Baijiu is based on the application of a series of optimized pure strains, namely, Bran Qu, the mixture of Daqu and Bran Qu is used as a saccharifying starter in sesame flavor Baijiu; hence, the main microorganisms and their metabolic pathways in the fermentation process of sesame flavor Baijiu are clearer and easier to control. In addition, the dependence of sesame flavor Baijiu quality on the environment is much lower than strong flavor and sauce flavor because the microorganisms involved in strong or sauce flavor Baijiu brewing are completely originate from the environment, whereas the microorganisms involved in sesame flavor Baijiu brewing are partly derived from pure strains [ 8 ]; therefore, the brewing process of sesame flavor Baijiu is more controllable, and the stability of the liquor quality is also improved.…”
Section: Introductionmentioning
confidence: 99%